Precisely integrated contact lens: An intraocular pressure guard for glaucoma patients - Ran Meixin; Yan Jiaqi; Zhang Hongbo (KeAi Communications Co., 2025)
Recently, scientists at Pohang University of Science and Technology in South Korea constructed a smart theranostic contact lens. The highly integrated smart contact lens is composed of an intraocular pressure (IOP) biosensor, a drug delivery system (DDS), a wireless communication system, as well as a circuit chip for IOP regulation. This design provides a new opportunity for wearable medical treatment in the individualized treatment of glaucoma and other ocular diseases.